Evolution of some Inflammatory Parameters and Tumor necrosis factor Alpha in Iraqi Postmenopausal Women with Hypertension - Jassim, Abeer M.; Hussain, Zainab K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Hypertension is a global health concern, with women experiencing lower blood pressure during their reproductive cycle and postmenopausal women being more sensitive to it. Postmenopausal women’s higher body mass increases the risk of hypertension, coronary artery disease, and death. Venous blood was taken from women of experimental groups by syringes into GEL tubes. Blood serum was obtained after allowing the blood to clot in the tube without anticoagulant for 10-20 min at room temperature. To calculate (TNF-alpha, CRP) for all samples, serum separation was done by centrifuge machine at 3000rpm for five minutes. C-reactive protein (CRP) kit and (TNF-alpha) kit by using the ELISA technique according to the manufacturer’s instructions of MyBio Source USA kit. The results showed that there was no significant variation in age (T-test) value (2.348) in postmenopausal women in the mean of patients (59.45±0.68) years, while healthy women were (57.50±0.97). There were significant changes in body mass index (BMI) in postmenopausal women (p≤0.01) that were found between the mean of patients (28.19±0.59) and the control group (25.65±0.19). Also, there were significant changes (p≤0.01) in the mean values of blood pressure diastole (8.76±0.06) and systole (16.00±0.15) in postmenopausal women compared with the control group with mean values (7.73±0.12) and (11.60±0.14), sequentially. Significant difference (p≤0.01) in mean value of HB patient women (12.89±0.16) as compared with healthy women (12.32±0.24). No significant changes in mean value of platelets (253.90±970) and WBCs (7.97±0.39) in patient postmenopausal women with control group (251±12.34) and (7.87±0.32), respectively. Significant change (p≤0.01) in mean value of TNF-alpha patient women (146.79±4.45) as compared with control (66.13±1.32). CRP show a significant difference (p≤0.01) in mean value, with patients being women (2.37±0.10) while the control group was (0.813±0.04). There was no significant change in the ESR mean of patients who were women (34.31±3.02) and the control group (31.40±3.02)